Structure, DNA Binding and Cytotoxicity Studies of [Cu(D-glu)(phen)(H2O)]•NO3•2H2O - Liu, Ling; Mou, Jie; Zheng, Youguang; Huang, Tonghui; Wang, Shuaishuai; Liu, Yi (Letters in Drug Design & Discovery, 2015)
A new complex [Cu(D-glu)(phen)(H2O)]·NO3·2H2O 1 (D-glu = D-glutamic acid, phen = 1,10-phenanthroline) was synthesized and identified by IR spectroscopy and single-crystal X-ray diffraction. Fluorescence studies showed that 1 exhibited stronger intercalative interaction to CT-DNA as compared to known complex [Cu(L-glu)(phen)(H2O)]·NO3·2H2O 2. Both complexes inhibited the growth of MCF-7 cells with the IC50 values of 0.141 μmol·L-1 and 0.126 μmol·L-1 for complex 1 and 2, respectively. The complexes were 20 times more active than the amino acid - free complex [Cu(phen)(H2O)2(NO33)] · NO3 3.
Keywords: [Cu(D-glu)(phen)(H2O)] • NO3 • 2H2O